Histopathological analysis of testicular lesions- a three year experience in a tertiary care center, Telangana - Dr. Aruna Tekumalla; Dr. Sreedhar Ragi; Dr. Ravinder Thota (Tropical Journal of Pathology and Microbiology, 2019)
Introduction: Testicular lesions can be of varied etiologies including non-neoplastic and neoplastic lesions. Non-neoplastic lesionsare most common compared to neoplastic lesions. Inflammatory lesions, torsion, atrophy and cryptorchidism are major non-neoplastic conditions. Germ cell neoplasms, among which seminoma is the most common malignancy. Though rare, incidence of these neoplasms is on rise for the past 1 or 2 decades in western countries. Aim and Objectives: Thisstudy is undertaken to analyse all the testicular lesions reported in CAIMS, Karimnagar, which is atertiary care center in Telangana and to see the incidence of testicular neoplasms in this region. Materials and Methods: This is a retrospective study of 3 year period from July 2015 to June 2018. Total of 80 cases have been studied and analyzed descriptively. Results: Out of 80 cases 65 were non-neoplastic and 15 were neoplastic lesions. Non specific Epididymoorchitis is the most common non-neoplastic lesion followed by testicular atrophy with maturation arrest. Seminoma is the most common malignant tumor followed by seminomatous mixed germ cell tumor. Conclusion: Our study is mostly comparable with the other studies.